2019
DOI: 10.1016/j.cma.2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Highly accurate acoustic scattering: Isogeometric Analysis coupled with local high order Farfield Expansion ABC

Abstract: This work is concerned with a unique combination of high order local absorbing boundary conditions (ABC) with a general curvilinear Finite Element Method (FEM) and its implementation in Isogeometric Analysis (IGA) for time-harmonic acoustic waves. The ABC employed were recently devised by Villamizar, Acosta and Dastrup [J. Comput. Phys. 333 (2017) 331] . They are derived from exact Farfield Expansions representations of the outgoing waves in the exterior of the regions enclosed by the artificial boundary. As a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 25 publications
(63 reference statements)
1
4
0
Order By: Relevance
“…This fact confirms the arbitrary high order character of the KFE-ABC that was claimed in [33]. Actually, this high order property was already observed in [41] where the KFE-ABC was combined with a high order isogeometric finite element method employed as a Helmholtz solver for the interior.…”
Section: Concluding Remarks and Future Worksupporting
confidence: 81%
See 2 more Smart Citations
“…This fact confirms the arbitrary high order character of the KFE-ABC that was claimed in [33]. Actually, this high order property was already observed in [41] where the KFE-ABC was combined with a high order isogeometric finite element method employed as a Helmholtz solver for the interior.…”
Section: Concluding Remarks and Future Worksupporting
confidence: 81%
“…They reached only fourth order convergence for circular obstacles. More recently, Tahsin and Villamizar [41], formulated an overall arbitrary high order method for acoustic scattering combining a finite element implementation in isogeometric analysis (IGA), which uses arbitrary high order non-uniform rational B-splines (NURBS) as a basis, with the high order local farfield expansions ABC employed in this study. Their experiments corroborated the overall high order convergence for high and very low frequencies (wavenumbers).…”
Section: Concluding Remarks and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach is to use enrichment techniques [65,66], but from the numerical study it is shown that the truncation error had higher influence than the discretization error. Khajah et al [67] employed the recently developed higher order local ABC based on the Karp's far-field expansion (KFE) and Wilcox's far-field expansion (WFE) within IGA for low to high frequencies for 2D and 3D problems, respectively. Unlike other ABCs, the salient feature of these higher order boundary conditions is that they do not require higher order derivative evaluations and hence impose no additional constraint on the regularity of the basis functions.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other ABCs, the salient feature of these higher order boundary conditions is that they do not require higher order derivative evaluations and hence impose no additional constraint on the regularity of the basis functions. This implies that the same basis functions can be used to estimate the field and the auxiliary ABC functions [67]. This is accomplished by introducing two families of auxiliary variables on the fictitious boundary.…”
Section: Introductionmentioning
confidence: 99%